Knowledge and Response to Stroke Among Lebanese Adults: A Population-Based Survey - Saade, Sylvia; Hallit, Souheil; Salameh, Pascale; Hosseini, Hassan (Frontiers in Public Health, 2022)
Objectives: To date, research on public awareness of stroke warning symptoms, risk factors and practice in the general adult population in Lebanon is scarce. The aim of our study is to identify the level of stroke awareness in order to develop and implement preventive measures particularly in relationship to primary stroke prevention. Methods: It is a cross-sectional study conducted among 410 adult participants from the five main governorates of Lebanon. Stroke knowledge and practice were assessed using two validated questionnaires namely the Stroke Knowledge Test (SKT) and the Stroke Action Test (STAT). Multivariable linear regression models were conducted to examine socio-demographic, social habits and clinical factors independently associated with the SKT and the STAT scores. Results: The mean SKT score of the participants was 9.16. 48.5% showed a poor stroke-related knowledge level and 51.5% a good knowledge level. Living in Mount Lebanon and occasional smokers showed statistically significant lower mean SKT scores; whereas, university degree and suffering from diabetes mellitus were associated with higher mean SKT scores. The mean overall STAT score was 41.3%. For 36.8% of the stroke symptoms, respondents selected call 112. The mean STAT scores of participants who get their information from the internet was statistically significantly lower. However, no association was found between the SKT score and the STAT score. Conclusion: Knowledge of stroke risk factors was low, as was awareness of the need to call 112 in response to stroke symptoms. Hence, it is essential to develop health education programs in order to decrease stroke morbidity and mortality. Keywords: stroke-knowledge-practice-awareness-Lebanon